Receptive human virtues a new reading of Jonathan Edwards's ethics - Cochran, Elizabeth Agnew, 1977- (University Park, Pa. : Pennsylvania State University Press, 2011)
"An examination of the writings on virtues and ethics of eighteenth-century Puritan Jonathan Edwards"--Provided by publisher.
An ethic of receptive human virtues -- Love as necessary and volitional : Edwards's account of true virtue in God -- Charity as a human virtue : the moral accountability of a necessary nature -- Humility as a human virtue : imaging God's mercy through creaturely capacities -- Virtuous repentance : apprehending and approving God's moral excellence -- Justice and partial loves : the natural goodness of incomplete virtues -- Conclusion: Virtues, accountability, and dependence : Edwards's significance for contemporary Christian ethics.
Revision of author's thesis (Ph. D.)--University of Notre Dame, 2007 under title: Revelations of love and operations of grace : Jonathan Edwards' human virtues.
Includes bibliographical references (p. [187]-193) and index.
Description based on print version record.
Keywords: Edwards, Jonathan, -- 1703-1758.; Virtues; Christian ethics -- United States; Christian ethics -- Puritan authors; RELIGION / Christian Theology / Ethics; Electronic books